2005
DOI: 10.3409/173491605775789281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Date of Egg-laying on the Biological Value of Eggs and Reproductive Traits in Pheasants (Phasianus colchicus L.)

Abstract: Pheasant eggs evaluated in the first period of egg-laying did not differ significantly in their weight and shape index and the values of both traits were, respectively, 30.7 to 32.2 g and 76.1 to 78.1%. Over the laying season the thickness of the shell decreased and its capacity for deformation and crush strength were greatest at the end of the laying season. The share of yolk in the egg was highest at the beginning of the laying season (35.3%), however over the peak of egg-laying and its final period the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 11 publications
(9 reference statements)
5
26
2
1
Order By: Relevance
“…With the passage of the reproductive season, the value of this trait increased in the research. A similar relationship was observed in pheasants by Kuzniacka et al (2005). In the literature, there are no publications about embryo mortality in eggs derived from pheasant hens kept in cages.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…With the passage of the reproductive season, the value of this trait increased in the research. A similar relationship was observed in pheasants by Kuzniacka et al (2005). In the literature, there are no publications about embryo mortality in eggs derived from pheasant hens kept in cages.…”
Section: Discussionsupporting
confidence: 75%
“…Kuzniacka et al (2005) also reported a high laying rate of pheasants at the peak of production. The fact that the reproductive performance of this species can vary was confirmed by Krystianiak et al (2007).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The shape index of pheasant eggs was determined as approximately 80% in various studies (Tserveni-Gousi and Yannakopoulos, 1990;Kırıkçı et al, 2003aKırıkçı et al, , 2004Kırıkçı et al, , 2005Kuzniacka et al, 2005). Shell weight is affected by egg color and hen age in pheasants (Kuzniacka et al, 2005;Günlü et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…W porównaniu z mięsem kurcząt brojlerów, kaczek czy gęsi, zawiera znacznie więcej jednonienasyconych kwasów tłuszczowych [5]. Mięśnie piersiowe bażantów zawierają 29 ÷ 47,9 mg cholesterolu/100 g, natomiast mięśnie nóg -67 ÷ 71,3 mg/100 g [7,23]. Zbliżoną zawartość cholesterolu mają mięśnie piersiowe (35,9 ÷ 43,1 mg/100 g) i mięśnie nóg (50,9 ÷ 76,1 mg/100 g) kurcząt brojlerów [20,21].…”
unclassified